A Taxonomy of Asynchronous Instructional Video Styles - Chorianopoulos, Konstantinos (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2018)
Many educational organizations are employing instructional videos in their pedagogy, but there is a limited understanding of the possible video formats. In practice, the presentation format of instructional videos ranges from direct recording of classroom teaching with a stationary camera, or screencasts with voice-over, to highly elaborate video post-production. Previous work evaluated the effectiveness of several production styles, but there has not been any consistent taxonomy, which would have made comparisons and meta-analyses possible. Therefore, we need a taxonomy of instructional video formats that facilitates the understanding of the landscape of available instructional video production styles. For this purpose, we surveyed the research literature and examined contemporary video-based courses, which have been produced by diverse educational organizations and teachers across several academic disciplines. We organized instructional video styles in two dimensions according to the level of human presence and to the type of instructional media. In addition to organizing existing instructional videos in a comprehensive way, the proposed taxonomy offers a design space, which should facilitate choice, as well as the preparation of novel video formats.